Innovation of Population Administration Services During COVID-19 Pandemic - Dwi Herlinda; Trio Saputra; Eka Eka; Farah Fauzan (Institut Pemerintahan Dalam Negeri, 2023)
Abstract This research aims to analyze the innovation in population administration services during the COVID-19 pandemic and identify the obstacles faced by the Pekanbaru City Population and Civil Registration Service. These challenges include disruption to the server network, limited processing quotas, and a lack of public awareness regarding the innovation of the SIPENDUDUK website. The research adopts a qualitative method involving descriptive analysis, as well as data collection through interviews, observations, and documentation. The results show that innovation in the SIPENDUK Administration Services during the COVID-19 pandemic at the Pekanbaru City Population and Civil Registration Service has been successful. Meanwhile, network disruptions, limited process service quotas, and lack of socialization are obstacles to the SIPENDUDUK website as an innovation in population administration services during the pandemic. Keywords: Innovation; Population Administration Services; COVID-19 Abstrak Penelitian ini bertujuan untuk mengetahui dan menganalisis tentang bagaimana inovasi pelayanan administrasi kependudukan di masa pandemi Covid-19 serta apa saja yang menjadi kendala dalam inovasi pelayanan di Dinas Kependudukan dan Pencatatan Sipil Kota Pekanbaru. Hal ini karena adanya gangguan terhadap jaringan server, keterbatasan kuota proses serta kurangnya sosialisasi terhadap masyarakat tentang inovasi website SIPENDUDUK. Penelitian ini menggunakan Metode Penelitian Kualitatif dengan pendekatan deskriptif. Pengumpulan data menggunakan teknik wawancara, observasi dan dokumentasi. Hasil penelitian menunjukkan bahwa Inovasi Pelayanan Administrasi SIPENDUDUK di Masa Pandemi Covid-19 di Dinas Kependudukan dan Pencatatan Sipil Kota Pekanbaru sudah berjalan dengan baik. Gangguan pada jaringan, keterbatasan kuota layanan proses dan kurangnya sosialisasi menjadi kendala pada website SIPENDUDUK sebagai inovasi pelayanan administrasi kependudukan di masa pandemi. Kata kunci: Inovasi; Pelayanan Administrasi Kependudukan; Covid-19